Inflation in Colombia after COVID – 19 - Perez Fajardo, Natalia Vanessa (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
After COVID-19, Colombia has had to face changes in the inflation rate which has been affected by many factors, such as social distancing measures and stagnations in the supply of products that have increased certain prices. Additionally, the increase in the unemployment rate causes income to decrease and both companies and employees are affected by the production and/or provision of services, taking into account that inflation during and after the pandemic is the most persistent increases and in which The most noticeable change was health and food, continuous monitoring has been maintained for the balance and/or regulation of prices and inflation in the country.